2017
DOI: 10.1093/mnras/stx936
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the scatter in the spatially resolved star formation main sequence of local massive spiral galaxies

Abstract: We investigate the relation between star formation rate (SFR) and stellar mass (M * ) in sub-galactic (∼ 1kpc) scale of 93 local (0.01 < z < 0.02) massive (M * > 10 10.5 M ) spiral galaxies. To derive spatially-resolved SFR and stellar mass, we perform so-called pixelto-pixel SED fitting, which fits an observed spatially-resolved multiband SED with a library of model SEDs using Bayesian statistics approach. We use 2 bands (FUV and NUV ) and 5 bands (u, g, r, i, and z) imaging data from Galaxy Evolution Explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 43 publications
(39 reference statements)
6
58
0
Order By: Relevance
“…Recently, it has been found that kiloparsec-scale S SFR traces well with the underlying * S for star-forming galaxies (Sánchez et al 2013;Cano-Díaz et al 2016;Abdurróuf & Akiyama 2017;Hsieh et al 2017). This relation may be responsible for the observed tight correlation between the global SFR and * M .…”
Section: Resolved S Sfr Versus * S Relationmentioning
confidence: 94%
“…Recently, it has been found that kiloparsec-scale S SFR traces well with the underlying * S for star-forming galaxies (Sánchez et al 2013;Cano-Díaz et al 2016;Abdurróuf & Akiyama 2017;Hsieh et al 2017). This relation may be responsible for the observed tight correlation between the global SFR and * M .…”
Section: Resolved S Sfr Versus * S Relationmentioning
confidence: 94%
“…Since the discovery of the galaxy Main Sequence (MS) and the development of basic frameworks to describe a galaxy's position relative to it, much work has gone into determining the prevalence and influence of outflows relative to the MS (e.g., Chen et al 2010;Rubin et al 2014;Cicone et al 2016;Roberts-Borsani & Saintonge 2018;Concas et al 2019). The arrival of large IFU surveys such as MaNGA, SAMI and CALIFA, has also revealed a resolved MS (Sánchez et al 2013;Cano-Díaz et al 2016;González Delgado et al 2016;Abdurro'uf, & Akiyama 2017;Hsieh et al 2017;Maragkoudakis et al 2017), indicative of a link between small scale processes and the integrated properties of galaxies. As such, it is interesting to look at the prevalence and properties of outflows over such a resolved sequence.…”
Section: The Resolved σ Sfr -σ M * Planementioning
confidence: 99%
“…4.2) that usually span the range 0.7 − 1.1 despite using different SFR tracers and different redshift and stellar mass ranges for the analysis (i.e. Pérez et al 2013;Wuyts et al 2013;Hemmati et al 2014;Cano-Díaz et al 2016;González Delgado et al 2016;Abdurro'uf & Akiyama 2017;Abdurro'uf 2018;Hall et al 2018;Cano-Díaz et al 2019). It is worth noting that several of the literature works implement the orthogonal distance regression (ODR) method to find the location of the MS relation.…”
Section: Spatially Resolved Msmentioning
confidence: 99%
“…These results suggest that the global relation is set locally, possibly by the surface density of molecular gas (Lin et al 2017). Exploiting pixel-by-pixel Spectral Energy Distribution (SED) fitting, Abdurro'uf & Akiyama (2017) analysed the spatially resolved MS in a sample of 93 local massive galaxies on ∼ kpc scales. They find that the slope of the relation varies dramatically (from 0.3 to 0.99) depending on the range of Σ used for fitting, somehow recalling the bending of the MS observed in the integrated MS relation (e.g.…”
Section: Introductionmentioning
confidence: 99%